2015
DOI: 10.1103/physrevb.91.235436
|View full text |Cite
|
Sign up to set email alerts
|

Noncentrosymmetric plasmon modes and giant terahertz photocurrent in a two-dimensional plasmonic crystal

Abstract: We introduce and theoretically study the plasmon-photogalvanic effect in a planar noncentrosymmetric plasmonic crystal containing a homogeneous two-dimensional electron system gated by a periodic metal grating with an asymmetric unit cell. The plasmon-photogalvanic dc current arises due to the two-dimensional electron drag by the noncentrosymmetric plasmon modes excited under normal incidence of terahertz radiation. We show that the collective plasmon modes of the planar plasmonic crystal become strongly nonce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
0
19
0
8
Order By: Relevance
“…The ratchet effects are expected to be strongly dependent on the in-plane asymmetry of the electrostatic potential and near-field effects of the radiation diffraction [25,33,34,38]. To demonstrate the effect of the asymmetry and examine the ratchet effects in the vicinity of Dirac point, we studied samples with an interdigitated dual-grating structure [see Figs.…”
Section: B Photocurrents In Interdigitated Dual-grating-gates Graphementioning
confidence: 99%
See 1 more Smart Citation
“…The ratchet effects are expected to be strongly dependent on the in-plane asymmetry of the electrostatic potential and near-field effects of the radiation diffraction [25,33,34,38]. To demonstrate the effect of the asymmetry and examine the ratchet effects in the vicinity of Dirac point, we studied samples with an interdigitated dual-grating structure [see Figs.…”
Section: B Photocurrents In Interdigitated Dual-grating-gates Graphementioning
confidence: 99%
“…It is worth noting that the differential plasmonic drag [38] can be also viewed phenomenologically as a specific "linear" ratchet effect induced in a periodic graphene structure by the normally incident THz radiation with the electric field polarized perpendicular to the grating gate. We simulate the interaction of THz radiation incident normally upon the grating-gated graphene in the framework of a self-consistent electromagnetic approach based on the integral equation method described in detail in Ref.…”
Section: A Photocurrent In the Direction Normal To The Grating Stripesmentioning
confidence: 99%
“…Ratchet effects whose prerequisites are simultaneous breaking of both thermal equilibrium and spatial inversion symmetry can be realized in a great variety of forms and, in particular, as electric transport in semiconductor systems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recent experiments demonstrated that terahertz radiation induced ratchet effects can be efficiently excited in semiconductor quantum wells (QWs) [14,15,21,22] and graphene [23,24] with lateral superlattice structures.…”
Section: Introductionmentioning
confidence: 99%
“…На эффектив-ность выпрямления ТГц излучения за счет эффекта элек-тронно-дырочного плазмонного храповика влияет как геометрическая асимметрия графеновой структуры, так и взаимодействие пространственных гармоник электри-ческого поля разных порядков. Эффективное взаимодей-ствие пространственных гармоник электрического поля разных порядков возможно при возбуждении в струк-туре гибридных плазмонных резонансов в результате взаимодействия плазмонных мод разных плазмонных резонаторов в элементарной ячейке графеновой структу-ры [18,19]. В пространственно-асимметричной структуре в дополнение к " радиационным" плазмонным модам с волновым вектором, кратным ширинам плазмонных ре-зонаторов, k p = (2n − 1)π/w 1,2 , возбуждаются " неради-ационные" плазмонные моды, волновой вектор которых определяется соотношением k p = 2πn/w 1,2 [19], где n -номер плазмонной моды.…”
Section: международный симпозиум "unclassified
“…В первом плазмонном резонансе (на частоте 1 ТГц) и во втором резонансе (на частоте 2 ТГц) в данной структуре возбуждаются подзатворные плазмонные мо-ды под широким затвором, слабо взаимодействующие с другими плазмонными модами. В этом случае поля плазмонов обладают симметрией [19] и поэтому эффект плазмонного электронно-дырочного храповика опреде-ляется в основном пространственной геометрической асимметрией графеновой структуры, а именно продоль-ным смещением области с дырочной проводимостью относительно центра широкого затворного электрода (который определяет профиль электрического поля в структуре).…”
Section: результаты и их обсуждениеunclassified